1994
DOI: 10.1149/1.2054855
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Nitrogen‐Substituted Carbon  (  N  z  C 1 − z  )  in Li / Li (  N  z  C 1 − z  ) 6 Cells

Abstract: Nitrogen-containing carbons N~C~_z have been made from different precursors at temperatures between 850 and I050~ Their composition and structure have been studied by chemical analysis, powder x-ray diffraction, x-ray absorption spectroscopy, and Auger electron spectroscopy. These techniques show that some nitrogen has been incorporated substitutionally for carbon. Nitrogen affects the behavior of Li/Li(NzC~ ~)8 electrochemical cells in two ways. First, the irreversible capacity observed during the first elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(31 citation statements)
references
References 3 publications
1
29
1
Order By: Relevance
“…In addition to the formation of composite materials with metal oxide, the modification of carbon nanomaterials (e.g., graphene) with chemical dopants such as boron,394 phosphorous,395 and nitrogen,396 has been investigated to improve the specific capacity of carbon materials. Recently, Leela et al390 reported that the N‐doped graphene made by CVD method showed almost the double reversible discharge capacitance compared with that of pristine graphene.…”
Section: Carbon Nanotubes For Energy Storagementioning
confidence: 99%
“…In addition to the formation of composite materials with metal oxide, the modification of carbon nanomaterials (e.g., graphene) with chemical dopants such as boron,394 phosphorous,395 and nitrogen,396 has been investigated to improve the specific capacity of carbon materials. Recently, Leela et al390 reported that the N‐doped graphene made by CVD method showed almost the double reversible discharge capacitance compared with that of pristine graphene.…”
Section: Carbon Nanotubes For Energy Storagementioning
confidence: 99%
“…Chemically doped carbon materials often show substantially increased specific capacities in comparison with non-doped carbon materials. In recent years, phosphorus, 1 sulfur, 2 boron, 3,4 nitrogen [5][6][7][8][9][10][11][12][13][14][15][16] and boron-nitrogen 17 have been used as dopants to improve the electrochemical performance of carbon materials. Of these, nitrogen is attractive because its electronegativity (3.5) is higher than that of carbon (3.0) and because its atomic diameter is smaller.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to graphite, amorphous carbons have been studied as candidates for anode materials in LIBs because of their good chemical and thermal stabilities as well as high Li‐storage capacity 4–13. In addition, various heteroatoms such as phosphorus, sulfur, boron, and nitrogen have been used as dopants to modify the carbon structures in an effort to increase their lithium storage capacity 14–19. Among these heteroatoms, nitrogen is a very promising candidate because of its high electronegativity, small atomic diameter, and additional free electrons contributing to the conduction band of carbons.…”
mentioning
confidence: 99%